Erodible Time‐Dependent Colon Delivery Systems with Improved Efficiency in Delaying the Onset of Drug Release. Issue 11 (11th September 2014) - Del Curto, Maria Dorly; Palugan, Luca; Foppoli, Anastasia; Zema, Lucia; Gazzaniga, Andrea; Maroni, Alessandra
<x xml:space="preserve">Abstract</x> To prepare swellable/erodible time‐dependent colon delivery systems with improved efficiency in delaying drug release, the application of an outer Eudragit® NE film, which contained the superdisintegrant Explotab® V17 as a pore former, was attempted. Tablet cores were successively spray‐coated with a hydroxypropyl methylcellulose (HPMC) solution and diluted Eudragit® NE 30 D, wherein fixed amounts of Explotab® V17 were present. The resulting two‐layer systems yielded lag phases of extended duration as compared with formulations provided with the HPMC layer only. By raising the thickness of the outer film, longer lag times were generally observed, whereas the effectiveness in deferring the drug liberation was reduced by increasing the pore former content, which, however, also resulted in a lower data variability. The films containing 20% of Explotab® V17 effectively and consistently prolonged the in vitro lag phase imparted by HPMC as a function of their thickness. Stored for 3 years under ambient conditions, a two‐layer system with this outer film composition pointed out unmodified release patterns. The same system proved to meet gastroresistance criteria when enteric coated. The results obtained indicated that the proposed strategy would enable the preparation of erodible delivery systems with reduced size, possibly suitable as multiple‐unit dosage forms. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3585–3593, 2014